Automated synthesis of N‐(2‐[18F]Fluoropropionyl)‐l‐glutamic acid as an amino acid tracer for tumor imaging on a modified [18F]FDG synthesis module. (12th May 2017) - Liu, Shaoyu; Sun, Aixia; Zhang, Zhanwen; Tang, Xiaolan; Nie, Dahong; Ma, Hui; Jiang, Shende; Tang, Ganghua
Abstract : N ‐(2‐[ 18 F]Fluoropropionyl)‐l ‐glutamic acid ([ 18 F]FPGLU) is a potential amino acid tracer for tumor imaging with positron emission tomography. However, due to the complicated multistep synthesis, the routine production of [ 18 F]FPGLU presents many challenging laboratory requirements. To simplify the synthesis process of this interesting radiopharmaceutical, an efficient automated synthesis of [ 18 F]FPGLU was performed on a modified commercial fluorodeoxyglucose synthesizer via a 2‐step on‐column hydrolysis procedure, including 18 F‐fluorination and on‐column hydrolysis reaction. [ 18 F]FPGLU was synthesized in 12 ± 2% (n = 10, uncorrected) radiochemical yield based on [ 18 F]fluoride using the tosylated precursor2 . The radiochemical purity was ≥98%, and the overall synthesis time was 35 minutes. To further optimize the radiosynthesis conditions of [ 18 F]FPGLU, a brominated precursor3 was also used for the preparation of [ 18 F]FPGLU, and the improved radiochemical yield was up to 20 ± 3% (n = 10, uncorrected) in 35 minutes. Moreover, all these results were achieved using the similar on‐column hydrolysis procedure on the modified fluorodeoxyglucose synthesis module. Abstract : An efficient and straightforward 2‐step on‐column hydrolysis‐automated synthesis procedure of N ‐(2‐[ 18 F]Fluoropropionyl)‐l ‐glutamic acid was successfully developed on a modified commercial FDG synthesizer. By using the brominated precursor in the radiosynthesis, this new method could give higher radiochemical yield (20 ± 3%, uncorrected) and shorter synthesis time (35 min) in the routine production of the target tracer.